Preference to Oil Spot or Oil Futures for Risk-Seekers - Hooi , Hooi Lean; Michael , McAleer; Wing , Keung Wong (Universiti Sains Malaysia, 2006)
This paper develops the stochastic dominance (SD) tests for risk seekers, We find both MV criterion and CAPM mesures unable to draw any conclusive preference between the returns but our SD results show that spot dominates futures in the downside risk while futures dominate spot in the upside profit. It also shows that the risk-averse investors prefer investing in spot index while risk seekers are attracted to futures index to maximize their utility, In addition, our SD results enable us to conclude that there is no arbitrage opportunity between these two prices and fail to reject market efficiency and market rationality.